A review of the current status of graphitic carbon nitride. Issue 3 (4th May 2021) - Rono, Nicholas; Kibet, Joshua K.; Martincigh, Bice S.; Nyamori, Vincent O.
Abstract: Graphitic carbon nitride (g-C3 N4 ) has become an important material because of its attractive optoelectronic properties. It has been applied in various fields such as photovoltaics, biosensing, and photocatalysis. As an analog of graphene, it has layers which can be transformed into different morphologies including nanosheets, nanotubes, and quantum dots. Pristine g-C3 N4 exhibits a low specific surface area and a high rate of recombination of photogenerated charges. Therefore, modification is required in order to improve its properties, for instance, by doping it with other atoms and transforming it into another morphology. In this review, the synthesis, modifications, and applications of g-C3 N4 are evaluated. The use of theoretical strategies to understand various properties of g-C3 N4 and its composites is highlighted. Moreover, the current status on the application of g-C3 N4 is explored. Ultimately, this review will shed more light on the uses and modifications of g-C3 N4 for future applications.